SHALLOW SEISMIC REFLECTION SURVEY FOR IMAGING DEEP-SEATED COAL LAYER - CASE STUDY FROM MUARA ENIM COAL - Muhammad Rizki Ramdhani; Muhammad Abdurachman Ibrahim; Hans E. A. Siregar; Tony Rahadinata (Puslitbang tekMIRA, 2021)
Indonesia has a great potential for deep-seated coal resources. To assist and support the deep-seated coal exploration, a shallow seismic reflection method is applicable for this purpose. This study has conducted a shallow seismic reflection method in Musi Banyuasin Regency, South Sumatera Province. The Muara Enim coal target varies from 100 to 500 meters from the surface. The thickness of the coal layer varies from 2 to 10.65 meters. This study uses 48 channels with 14 Hz single geophone and Mini-Sosie as the energy source. The receiver and source interval is 15 meters. This study uses a fixed receiver and moving source configuration. From the interpreted seismic section, this study identified a deep-seated coal layer target. These layers are Mangus, Burung, Benuang, Kebon and Benakat layers. A simple interpretation is analyzed by combining the seismic amplitude characteristics and the thickness of the coal layer from the borehole data. From the interpreted seismic section, deep-seated coal layer targets have strong amplitude characteristics and are continuous from southwest to the northeast with a down-dip of around 20-30°. This study helps to inform the operator companies who develop the utilization of deep-seated coal (coalbed methane, underground coal gasification and underground coal mining) about the effective and proper geophysical method for imaging deep-seated coal layer.